2017
DOI: 10.1002/ijc.31072
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNA‐26b‐5p and its target TRPS1 is associated with radiation exposure in post‐Chernobyl breast cancer

Abstract: Ionizing radiation is a well-recognized risk factor for the development of breast cancer. However, it is unknown whether radiation-specific molecular oncogenic mechanisms exist. We investigated post-Chernobyl breast cancers from radiation-exposed female clean-up workers and nonexposed controls for molecular changes. Radiation-associated alterations identified in the discovery cohort (n = 38) were subsequently validated in a second cohort (n = 39). Increased expression of hsa-miR-26b-5p was associated with radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…MiRNA-induced suppression of gene expression mainly occurs at the posttranscriptional level. 3537 We searched databases (microRNA.org and TargetScan) and found that miR-133a-3p, a tumor suppressor in some tumors, 38,39 could directly target MYH9. Furthermore, we confirmed that miR-133a-3p, a tumor suppressor, directly downregulated MYH9 protein expression by binding to its 3’UTR in NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-induced suppression of gene expression mainly occurs at the posttranscriptional level. 3537 We searched databases (microRNA.org and TargetScan) and found that miR-133a-3p, a tumor suppressor in some tumors, 38,39 could directly target MYH9. Furthermore, we confirmed that miR-133a-3p, a tumor suppressor, directly downregulated MYH9 protein expression by binding to its 3’UTR in NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miRNAs, which are associated with multiple facets of cellular activities, is one of the most important and exciting emerging paradigms in cell biology. Accumulating genetic evidence indicates that miRNAs also play an essential part in stress responses, such as hypoxia, hydrogen peroxide (H 2 O 2 ) and ionizing radiation (IR) (2)(3)(4)(5). For example, it has been reported that several miRNAs are regulated by IR treatment (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Equally, the overexpression of miR‐182 confers radioresistance in non‐small‐cell lung cancer (Chen et al , ). In addition, mir‐26b increased in radiation‐associated BC in female post‐Chernobyl clean‐up workers in comparison with nonexposed control (Wilke et al , ). These miRNAs related to radiation exposure associated with DNA damage response and tumor progression could represent radiation markers in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, miRNA expression changes could be useful for monitoring exposures and understanding regulation in response to radiation‐induced DNA damage (Cellini et al , ; Czochor and Glazer, ); for example, studies have shown that miR‐125b and miR‐139 could be useful biomarkers of radiosensitivity (Metheetrairut et al , ; Pajic et al , ). Alike, it has been observed that the overexpression of miR‐26‐5p after radiation exposure is related to processes of breast carcinogenesis or that the miR‐223 expression (a potential tumor suppressor) in BC patients after radiation treatment restrains recurrence formation via EGF/EGFR pathway (Fabris et al , ; Wilke et al , ). For these reasons, miRNAs could be good cancer biomarkers for diagnostic, prognostic, and treatment response that could improve the efficacy of current cancer therapy (Halvorsen et al , ; Schwarzenbacher et al , ).…”
Section: Introductionmentioning
confidence: 99%